HAMBATAN UMKM DI KOTA KUPANG BELUM MENERAPKAN SAK EMKM - Suryaningsi; Sari, Deanita (Al-Buhuts, 2024)
The purpose of this study is to determine what obstacles are faced or felt by MSME actors in using SAK EMKM. Based on the results of observations, most MSME actors in Kupang City still prepare financial reports without using SAK EMKM. This qualitative research uses qualitative methods with descriptive data collection methods, namely in-depth interviews and interactive observations. In addition, the data analysis method used is narrative analysis. The results of the research found several obstacles, namely that MSME actors did not know about accounting and what SAK EMKM was, lack of socialization carried out by the Cooperative and SME Service regarding accounting knowledge and SAK EMKM, MSME actors felt that accounting was very difficult, the human resources they had were inadequate and not competent, There is no time to make or present correct bookkeeping, MSMEs have difficulty and do not know who to contact to learn or help make good financial reports, MSMEs think that the simple bookkeeping that has been done is already included in the form of a financial report , and there is a perception that it is better to carry out bookkeeping or recording using a method that is simple and easier to understand while not affecting the sustainability of the business being run.